Market-Based Housing Reforms and the Residualization of Public Housing: The Experience of Lodz, Poland - Ogrodowczyk, Agnieszka (2021)
Housing inequality is one of the central topics in urban studies, and in the social sciences more broadly. It is also one of the most significant and visible aspects of socioeconomic inequality. Over the last three decades, the process of housing commodification has accelerated across western societies and, consequently, the public housing sector has contracted and become more closely associated with the poorest sections of societies in many cities. Over the same period, the political changes in Central and Eastern Europe have contributed to the dismantling and monetizing of state housing sectors at the forefront of broader social and economic transformations. Unfortunately, most recent studies on housing commodification and inequalities in Europe are confined to the national scale. The aim of this article is to detail the linkages between the position and functioning of public housing in Lodz (Poland) and the evolving socioeconomic profile of individuals and households that rely on public housing. This study relies on microdata (statistical information on individuals and households) from two national Polish censuses (1978 and 2002) and from household budget surveys (2003–2013). The main finding of our study is that ‘residualization’ is present in the public housing stock in Lodz and that the process gained momentum in the first decade of the 2000s.